مشاكـــل العقــــود الدوليـــة الإلكترونيـــة (El-Wahat Journal for Research and Studies, 2017)
Modern Technological Revolution Has Given Birth To New Mechanisms Governing Different Aspects Of Individuals’ Life And Agreements. So, A New Type Of International Online Agreements Has Emerged, Having In Common With The Traditional Agreements, The General Terms And Conditions In Matter Of Acceptance, Place And Motives, And Differing From Them In Matter Of Contracting Means And Virtual Space In Which They Are Concluded, As Well As The Difficulty To Identify The Place. Such Type Of Agreements Creates New Problems Regarding Identification Of The Laws To Be Implemented And The Suitable Regulator According To The Parties’ Desire And The Agreement Nature, In Addition To Another Problem Consisting In The Assignment Of The Competent Judge And Court To Settle Such Conflicts Related To International Electronic Agreements. Keywords –  Electronic Contracts - Virtual Space - The Laws To Be Implemented - Suitable Regulator - The Competent Judge - Court To Settle Such Conflicts